2020
DOI: 10.1370/afm.2471
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Interactive Website to Engage Patients in Advance Care Planning in Outpatient Settings

Abstract: PURPOSE Online programs may help to engage patients in advance care planning in outpatient settings. We sought to implement an online advance care planning program, PREPARE (Prepare for Your Care; http://www. prepareforyourcare.org), at home and evaluate the changes in advance care planning engagement among patients attending outpatient clinics. METHODS We undertook a prospective before-and-after study in 15 primary care clinics and 2 outpatient cancer centers in Canada. Patients were aged 50 years or older (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
0
15
1
1
Order By: Relevance
“…That said, given the current heterogeneity of ACP outcomes, future research should consider using some standardized outcomes so that trial findings can be compared, as some studies are attempting 154,155 . Finally, pragmatic trials measuring implementation strategies in real‐world settings are needed, and several are underway 152,154‐156 . For effective ACP interventions, an impartial repository, as used in other fields, 157 may help disseminate the interventions to clinical champions.…”
Section: Discussionmentioning
confidence: 99%
“…That said, given the current heterogeneity of ACP outcomes, future research should consider using some standardized outcomes so that trial findings can be compared, as some studies are attempting 154,155 . Finally, pragmatic trials measuring implementation strategies in real‐world settings are needed, and several are underway 152,154‐156 . For effective ACP interventions, an impartial repository, as used in other fields, 157 may help disseminate the interventions to clinical champions.…”
Section: Discussionmentioning
confidence: 99%
“…To support community‐based ACP conversations, the study results suggested the importance of online ACP resources. There are existing Web‐based ACP models developed in Western countries such as the USA, Ireland and Australia 47–49 . A previous study suggested that it is essential that important ACP information be included in the Electronic Health Record so that multiple clinicians, even from different healthcare organizations, can retrieve them, understand what is most important to patients, clarify their preferences for end‐of‐life care, and review all documents regularly to make sure they still accurately reflect their wishes 50 .…”
Section: Discussionmentioning
confidence: 99%
“…[17] The survey has been used as an outcome in several studies examining the impact of ACP interventions. [23,20,21] The ACP-55 question stems were reworded to apply to SDMs and then examined by an 8person panel of ACP researchers, clinicians, and laypersons for face validity. Resultantly, 8 items were removed and 6 items flagged for re-evaluation after data collection.…”
Section: Phase 1: Adapting the Original Acp Engagement Survey For Usementioning
confidence: 99%
“…We opted not to change the wording of the question stems from the original survey because these stems were generated from focus groups including both patients and surrogates and the original survey was vetted extensively by patients. [18,23] Since our goal was to align the survey as closely as possible to the well-validated ACP-55, stems were kept as close to the original as possible.…”
Section: Phase 1; Adaptation Of the Acp-55 And Review For Face Validitymentioning
confidence: 99%